Matrine Reverses the Warburg Effect and Suppresses Colon Cancer Cell Growth via Negatively Regulating HIF-1α - Hong, Xiaoting; Zhong, Linhai; Xie, Yurou; Zheng, Kaifeng; Pang, Jinglong; Li, Yesen; Yang, Yifan; Xu, Xiaolin; Mi, Panying; Cao, Hanwei; Zhang, Wenqing; Hu, Tianhui; et al. (Frontiers in Pharmacology, 2019)
The Warburg effect is a peculiar feature of cancer’s metabolism, which is an attractive therapeutic target that could aim tumor cells while sparing normal tissue. Matrine is an alkaloid extracted from the herb root of a traditional Chinese medicine, Sophora flavescens Ait. Matrine has been reported to have selective cytotoxicity towards cancer cells but with elusive mechanisms. Here, we reported that matrine was able to reverse the Warburg effect (inhibiting glucose uptake and lactate production) and suppress the growth of human colon cancer cells in vitro and in vivo. Mechanistically, we revealed that matrine significantly decreased the mRNA and protein expression of HIF-1α, a critical transcription factor in reprogramming cancer metabolism towards the Warburg effect. As a result, the expression levels of GLUT1, HK2, and LDHA, the downstream targets of HIF-1α in regulating glucose metabolism, were dramatically inhibited by matrine. Moreover, this inhibitory effect of matrine was significantly attenuated when HIF-1α was knocked down or exogenous overexpressed in colon cancer cells. Together, our results revealed that matrine inhibits colon cancer cell growth via suppression of HIF-1α expression and its downstream regulation of Warburg effect. Matrine could be further developed as an antitumor agent targeting the HIF-1α-mediated Warburg effect for colon cancer treatment.